2015
DOI: 10.4103/2229-5178.153006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levels of serum copper, zinc, albumin, globulin and alkaline phosphatase in psoriatic patients and controls: A hospital based casecontrol study

Abstract: Background:Psoriasis is a chronic, immune-mediated skin disease with unknown etiology, with an epidermal turnover time of <10 days compared to a normal turnover time of 4-8 weeks. This epidermal hyperproliferation accounts for many of the metabolic abnormalities including alteration in the serum levels of proteins and some trace elements.Aim:The aim was to detect any statistically significant difference in the serum levels of zinc, copper, albumin, globulin and alkaline phosphatase between psoriasis patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
4
20
1
2
Order By: Relevance
“…There was no statistically significant difference between the ML group and the control group (p < 0.05) [11]. In another study evaluating patients with psoriasis, serum Cu levels were found to be significantly higher in the psoriasis group (p < 0.0001) [13]. In a similar way, serum Cu values obtained in our study were found to be significantly higher in the SD group than in the control group.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There was no statistically significant difference between the ML group and the control group (p < 0.05) [11]. In another study evaluating patients with psoriasis, serum Cu levels were found to be significantly higher in the psoriasis group (p < 0.0001) [13]. In a similar way, serum Cu values obtained in our study were found to be significantly higher in the SD group than in the control group.…”
Section: Discussionsupporting
confidence: 75%
“…The authors concluded that Zn, which acts as a cofactor for metalloenzymes in many cellular pathways, can be used in the treatment of acne due to its anti-inflammatory activity. In another study by Sheikh et al [13] in patients with psoria- sis, it was found that serum Zn levels were significantly lower in the psoriatic group than in the control group (p < 0.0001). In a study, in which serum Zn was investigated in a patient group with SD, although serum Zn level was higher in the SD group than in the control group, no statistically significant difference was found between the two groups (p = 0.507) [14].…”
Section: Discussionmentioning
confidence: 88%
“…1 ). Increased levels of copper [ 95 , 96 ] and free reactive iron [ 34 ] were found in psoriatic patients. When comparison of copper data was done between groups of psoriasis severity, a significant difference was found between mild, moderate and severe groups [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Found 14,21 significantly raised serum alkaline phosphatase levels in psoriasis cases 17,22 whereas found no significant alteration in serum alkaline phosphatase levels in psoriasis patients. The finding in our study is in concordance with these latter studies.…”
Section: Alkaline Phosphatasementioning
confidence: 84%
“…Oxidative stress is a known risk factor for exacerbation of psoriasis. Metalloenzymes such as alkaline phosphatase and Superoxide dismutase reduce the oxidative stress 17 . Serum alkaline phosphatase level is a marker of oxidative stress in body.…”
Section: Discussionmentioning
confidence: 99%